EFEK NUMBER OF ITEM DAN SAMPLE SIZE TERHADAP AKURASI ABILITY ESTIMATION PADA MODEL IRT TIGA PARAMATER LOGISTIK - Samritin Samritin (JEC (Jurnal Edukasi Cendekia), 2018)
This study aims to determine the effect of the number of items and sample size on the estimated accuracy of the 3PL IRT Model. This research is a simulation research that uses three variations of the number of items, namely 30, 40, and 60 with three variations of the sample size, namely 500, 750, and 1000. The research data is obtained from the results generated by a computer application program. The data obtained were analyzed descriptively using the correlation coefficient, mean square difference (MSD), and bias. The results of this study indicate that based on the correlation coefficient the highest accuracy was obtained at N=1000 with n=60 but the lowest MSD was obtained at N=750 and n=60, the lowest bias was at N=500 and n=60. Based on the results of the MSD analysis and the bias of this study it was concluded that sample size has an unadjusted effect on estimation ability. This study also found that the more items tested, the more accurate the estimation of the ability of the test takers